THE USE OF DISCOVERY LEARNING METHOD TO INCREASE MOTIVATION AND STUDY RESULT OF STUDENT AT STUDY PROGRAM OF BUILDING ENGINEERING EDUCATION - Sitinjak, Tarita Aprilani (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
Good motivation and study result of student is one of the purposes of courses. To increase them requires not only good facility but also the learning methods which appropriate and fun. The purpose of this research is to increase the motivation and learning achievement of the third-semester students in Study Program of Building Engineering Education who took engineering mechanics subject by using Discovery Learning Method. Descriptive analysis was used to figure out the student’s perception on the research variables. Lecture Activity Unit (SAP) and student’s work sheets, in individual or in group, were used as a research instrument. From the result analysis it is concluded that the average mark of learning achievement on the first cycle is 59.57 with the percentage of completion of 35.71%, and for incompletion percentage is 64,29%. The highest mark on first cycle is 78, meanwhile the lowest mark is 48. Furthermore, the second cycle shows that the average mark is 73 with the percentage of completion is 92,86%, on the other hand, for incomplete is 7,14%. In this cycle the highest mark is 92 and the lowest is 59. In the learning process, there is also a significant increase from 3 become 3.5, which means the learning process runs more dynamics and the learning organizations are better.